Implikasi Pembatasan Usia Perkawinan terhadap Dispensasi Kawin - Amsari Damanik (Jurnal Syntax Transformation, 2021)
Marriage is a very sacred bond in human life, so this is what distinguishes humans as the most perfect creatures from reptiles, furthermore that marriage in Islam is not merely a relationship or civil contract, but marriage is the sunnah of the Prophet Shallalhi'laihiwasalam, as well as means of getting closer to Allah because marriage will create a sense of calm in navigating life, however, in order to carry out a marriage, legally it must meet the formal requirements that have been stipulated by law. men and women are equal, namely 19 (nineteen years) on the other hand there is a legal loophole in the law, so that those under 19 years of age can get married by submitting a marriage dispensation to the Religious Court, what are the considerations and legal implications of being rejected at the Religious Courts. spensation of marriage by the judge.